Knights in Kampala: Ride Again - Rutiba, Patricia.K (Uganda: Self Published, 2020)
Read the second and last book in the knights series to find out: What happens after Byron rescues Briana? Who is behind the human resource disaster in MK's Accounting firm? Mark discovers that his efforts to be an excellent professional have attracted a powerful client, to more than just his IT skills. What does one do when unemployment and compromise seem to be one's only options? follow the drama that ensures when family and friends get to know about the ongoing courtships. How family and office politics threaten to destroy the relationships, before they even settle to plan the walk down the aisle. Will Carol and Mark go ahead with their wedding plans when a skeleton-in-the-closet crawls out and gives Carol the fright of her life?Will Byron fall apart when catastrophic family event threatens his very sanity? Their faith blooms during the beautiful, breathtaking moments they share as couples, but where is God when they need him most; when everything is crashing down around them...
Read the second and last book in the knights series to find out: What happens after Byron rescues Briana? Who is behind the human resource disaster in MK's Accounting firm? Mark discovers that his efforts to be an excellent professional have attracted a powerful client, to more than just his IT skills. What does one do when unemployment and compromise seem to be one's only options? follow the drama that ensures when family and friends get to know about the ongoing courtships. How family and office politics threaten to destroy the relationships, before they even settle to plan the walk down the aisle. Will Carol and Mark go ahead with their wedding plans when a skeleton-in-the-closet crawls out and gives Carol the fright of her life?Will Byron fall apart when catastrophic family event threatens his very sanity? Their faith blooms during the beautiful, breathtaking moments they share as couples, but where is God when they need him most; when everything is crashing down around them...